2011
DOI: 10.1111/j.1463-1318.2010.02469.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical resection in Crohn’s disease: is immunosuppressive medication associated with higher postoperative infection rates?

Abstract: There was no difference in the rate of postoperative complications among the groups of patients undergoing surgery for CD pretreated with IFX or other immunosuppressive drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 13 publications
1
60
1
2
Order By: Relevance
“…Canedo et al concluded that there were no differences in the rate of post-operative complications among the groups of patients undergoing surgery for CD pre-treated with infliximab or other immunosuppressive drugs, but as it is difficult to determine the time window of follow-up period and the study does not provide risk estimates, the results are difficult to compare with our results. 13 Other studies on CD patients, including fewer exposed patients than the studies by Appau et al and Canedo et al, mainly concluded that pre-operative infliximab was not associated with post-operative complications. [14][15][16] When it comes to impact of the timing of treatment with the anti-TNF-a agents before surgery, there have been no studies solely on CD patients.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Canedo et al concluded that there were no differences in the rate of post-operative complications among the groups of patients undergoing surgery for CD pre-treated with infliximab or other immunosuppressive drugs, but as it is difficult to determine the time window of follow-up period and the study does not provide risk estimates, the results are difficult to compare with our results. 13 Other studies on CD patients, including fewer exposed patients than the studies by Appau et al and Canedo et al, mainly concluded that pre-operative infliximab was not associated with post-operative complications. [14][15][16] When it comes to impact of the timing of treatment with the anti-TNF-a agents before surgery, there have been no studies solely on CD patients.…”
Section: Discussionmentioning
confidence: 96%
“…Until now, the two largest studies that included solely CD patients are from Appau et al examining 60 patients exposed to infliximab within 3 months before surgery 12 and from Canedo et al examining 65 patients. 13 Appau et al concluded that infliximab used pre-operatively was associated with increased 30-day post-operative sepsis (adjusted OR = 2.62, 95% CI: 1.12-6.13), abscess (OR = 5.78, 95% CI: 1.69-19.7), and readmissions (adjusted OR = 2.33, 95% CI: 1.02-5.33). 12 Regarding the increased risk of abscess and sepsis, our data could not confirm these results -on the contrary -among our 214 operations for CD, we found no treatments of abscesses during 30 or 60 days of follow-up, and in our sub-analysis of bacteraemia, we found no increased risk after 30 days.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Применение инги-биторов фактора некроза опухоли (Tumor Necrosis Factor, ТNF) может быть ассоциировано с умеренным повышени-ем риска инфекционных постоперационных осложнений [14]. Вместе с тем азатиоприн не повышает риск развития осложнений и может использоваться как до, так и после хирургического вмешательства [15,16].…”
Section: вопросы современной педиатрииunclassified